Performance Measurement and Management in Oil and Gas Maintenance – Item Development - Mohd Idris, Mohd Hafiz; Raja Mamat, Tengku Nur Azila; Ahmad, Nurazwa; Azman, Nurul Afiqah; Shaari, Muhammad Farid; Tuan Ismail, Tuan Noor Hasanah (Research in Management of Technology and Business, 2025)
The oil and gas industry faces challenges such as volatile prices, political instability, and competition from renewables; underscoring the need for a robust maintenance performance measurement framework to enhance efficiency and cost management. This research focuses on determining maintainence performance measurement items by means of a systematic literature review (SLR). From 21 articles found using SLR, 14 possible performance measurement items were identified; including cost, safety, equipment reliability, and productivity. These items will be used as the input to the quantitative survey in determining the key performance measurement index for oil and gas maintenance in Malaysia. This framework then aims to support Malaysian oil and gas companies in achieving sustainable operations and enhanced performance amid market uncertainties.